Skupine učencev glede na izvajanje in/ali doživljanje medvrstniškega nasilja: vloga metode poročanja - Košir , Katja; Špes, Tanja (Celostni pristop k medvrstniškemu nasilju: Psihosocialni konteksti in raziskovalne strategije, 2025)
Perpetration and experience of violence are not independent constructs, so adolescents can be classified into different groups depending on the level of perpetration and/or experience of peer violence, i.e. bullies, victims, bully-victims and non-participants. The purpose of this paper is to determine groups based on self-reporting and/or peer reporting methods on the perpetration and experience of violence and to compare them in terms of individual characteristics. The results showed that the self-reporting or peer reporting method alone is not adequate for classifying participants, which indicates the key role of triangulation of data collection in researching peer violence. It was surprising to detect similar differences between groups that were identified using different methods. Bullies are primarily those who are perceived as highly popular, with high moral disengagement and at the same time with positive choices for socializing. The opposite is true for victims of violence, who report low peer support and good relationships with teachers. Bully-victims were somewhat more similar to bullies than to victims, but much depended on the reporting method. Non-participants have higher peer support and are perceived as prosocial. The results suggest that violence is an effective way to strengthen social status and gain peer support, which should be addressed by changing class norms.